Enhancing network complexity and function of soil bacteria by thiourea-modified biochar under cadmium stress in post-mining area. (September 2022) - Zhu, Yanfeng; Wang, Liping; You, Yunnan; Cheng, Yanjun; Ma, Jing; Chen, Fu
Abstract: Cadmium (Cd) pollution cause severe stress to soil microorganisms and biochar utilized for its ability to immobilize Cd in the soil effectively. However, the influence of biochar on the structure and function of the bacterial network under Cd stress is unclear. This research reports a pot experiment conducted to investigate the impact of 2.0% Italian poplar bark biochar (PB), 2.0% thiourea-modified biochar (TP), and control treatment (CK) on the complexity, stability and functional properties of the bacterial community under Cd stress. The results showed that: (1) Biochar increased the diversity of soil bacterial consortia under Cd stress ( p < 0.05), and the diversity index demonstrated as order of CK < PB < TP; (2) Compared with CK network, the nodes number of PB and TP treatments networks were much higher, while the modularity and transitivity increased by 0.04% and 37.6%, 2.45% and 1.12%, respectively. The biochar amendment increased the stability and complexity of the network; (3) PICRUSt2 prediction results show that Xenobiotics biodegradation and metabolism membrane transport of TP treatment increased 62.52% and 53.62% compared with CK, respectively, which could be related to the decrease in Cd content according to principal component analysis. (4) The reduction of leaching Cd content caused network complexity and bacterial function changes by biochar amendment. TP amendment enhanced the complexity and stability of soil bacterial community under Cd stress, which will provide a scientific basis for in situ remediations of Cd-contaminated soils. Graphical abstract: Image 1 Highlights: Thiourea-modified biochar (TP) enhanced bacterial activities in Cd-contaminated soil. TP increased the complexity and stability of bacterial networks under Cd stress. TP improved the metabolic function of bacteria. TP relieved Cd stress on soil bacteria.